PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA CIJUJUNG, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Trihantana, Rully; Suryani, Ermi; Ananda, Della Rizki (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
This community service aims to build local potential in Cijujung Village so that it becomes an independent and advanced community. The subjects of this community service are the people of Cijujung Village, Cibungbulang District, Bogor Regency, West Java Province. In this community service, activities are carried out based on analytical methods in the field. The result of this community service is the existence of a new innovation in Cijujung Village, namely the G'Chips product, a food product made from double leaves which is one of the local potential plants of Cijujung Village. With this dedication to the community, it can be concluded that new innovations have been created in Cijujung Village, especially for housewives to be more productive in managing the local potential of the Village, so that G'Chips (double leaf chips) were created to increase the Human Resources of Cijujung Village. quality and sustainable so as to improve the community's economy.